QRIS as a Single Payment Gateway as a Solution for Payment Efficiency and Legal Protection for e-commerce Consumers Through a Comparison With China - Matthew Jakaria Sitanggang; Imam Haryanto (Dinasti Research, 2025)
The increasing interest in shopping through e-commerce is accompanied by consumers' desire for easy, fast, and efficient payment methods, leading to a decline in cash usage as transactions can be conducted without spatial or temporal limitations through various payment gateways. In response to this phenomenon, Indonesia introduced a national payment gateway called QRIS. However, QRIS still faces several weaknesses, particularly in terms of effectiveness and consumer protection, which necessitate improvements. A single payment gateway is considered an effective solution to address these issues. This study used the statute approach and the comparative approach. It examined laws and regulations related to payment systems and consumer protection in e-commerce implemented in Indonesia, with China serving as a comparative study. The study results indicate that certain features of QRIS are not yet adaptive to current cutting-edge technologies, highlighting the need for more specific regulatory provisions in several Indonesian laws, particularly the importance of independent regulations governing e-commerce to create inclusivity in digital transactions.